Pengaruh E-WOM, Brand Image dan Brand Trust Terhadap Keputusan Konsumen (Studi Kasus Pada Lembaga Kursus Fajar English Course Pare-Kediri) - Ruhamak, Muhammad Dian; Rahmadi, Afif Nur (Universitas Islam Negeri Sunan Kudus, 2019)
This study aims to determine the effect of e-wom variables, brand image and brand trust on consumer decisions in institutions of the English course pare-kediri dawn courses. The population in this study were all consumers of English course dawn courses in August-September 2019 of 89 respondents, because less than 100 then the whole was taken to be sampled. Methods of data analysis using the validity and reliability of the questionnaire, multiple regression analysis, f and t test and the coefficient of determination. From the test results obtained e-wom variables, brand image and brand trust simultaneously have a positive and significant effect on consumer decisions with a value of fcount 41.919> 2.71 (fcount) and a significance value of 0.000. Partially e-wom and brand image have a positive and significant effect on consumer decisions with a tcount of 3.795> 1.99, 5.714> 1.99 and a significance of 0.000. While brand trust is negative and does not have a significant effect on consumer decisions with consumer values, this is based on test results that show a t-value of -1.625 <ttable 1.99 and a significance value of 1.08. Brand image has the most dominant influence on consumer decisions because it has the most influence.